Active sites for oxygen reduction reaction on nitrogen-doped carbon nanotubes derived from polyaniline. (February 2017) - Deng, Haijing; Li, Qian; Liu, Jingjun; Wang, Feng
Abstract: Understanding exact electronic configurations of carbon atoms bonded by nitrogen (N) functionalities at atomic-level may literally open a door to advance metal-free carbon materials as efficient catalysts for the oxygen reduction reaction (ORR). In this paper, a set of well-defined carbon nanotubes with controlled doping of various N species, such as pyrrolic, pyridinic and graphitic N, have been achieved by in-situ pyrolysis of polyaniline (PANI) nanotubes at different temperatures. Among these synthesized samples, the carbon nanotubes fabricated at 700 °C exhibit the highest electro-catalytic ORR activity, long-standing stability and good tolerance against methanol in alkaline medium. The improved activity is mainly attributed to the high nitrogen level of the active pyridinic and graphitic N. But, the pyridinic N possesses higher activity than the graphitic N because of their different sp 2 electronic structures. Pyridinic N, after bonding with two carbon(C) atoms, has two distorting N−C orbitals and one dangling orbital occupied by a lone electron pairs which are exposed, as the N sits at the edge of the carbon planes. Such unique electronic configuration makes the nitrogen and surrounding carbon atoms, bonded in the CN bonds, can serve host of active sites or work as active sites for the ORR. Graphical abstract: